2014
DOI: 10.1039/c4ta04221b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fe2+substitution on the structure and electrochemistry of LiCoPO4prepared by mechanochemically assisted carbothermal reduction

Abstract: LiCo 1Ày Fe y PO 4 solid solutions (0 # y # 1) were prepared by the mechanochemically assisted carbothermal reduction of Co 3 O 4 and Fe 2 O 3 . Mechanical activation was performed using a high-energy planetary mill AGO-2. The samples were characterized in detail by X-ray powder diffraction (XRD) using a Rietveld refinement, Fourier transform infrared spectroscopy (FTIR), M össbauer spectroscopy, scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), galvanostatic cycling, and galvanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 34 publications
9
45
0
Order By: Relevance
“…According to Kosova et al, 33 the peak related to the formation of the partly lithiated Co 2+ /Co 3+ couple intermediate phase disappears at higher Fe contents (y ≤ 0.5 in LiFe 1-y Co y PO 4 ), and a single-phase diffusional mechanism replaces the two-phase processes observed in LiFePO 4 and LiCoPO 4 . They also claimed that this would apply to all compositions y ≤ 0.…”
Section: Partially Delithiated Electrodes-the Effects Of Co and Ni Smentioning
confidence: 99%
See 3 more Smart Citations
“…According to Kosova et al, 33 the peak related to the formation of the partly lithiated Co 2+ /Co 3+ couple intermediate phase disappears at higher Fe contents (y ≤ 0.5 in LiFe 1-y Co y PO 4 ), and a single-phase diffusional mechanism replaces the two-phase processes observed in LiFePO 4 and LiCoPO 4 . They also claimed that this would apply to all compositions y ≤ 0.…”
Section: Partially Delithiated Electrodes-the Effects Of Co and Ni Smentioning
confidence: 99%
“…Kosova et al 33 Nyten et al 66 suggested that Co substitution at y < 0.75 levels does not lead to structure distortion, but a less stable structure would be found for y > 0.75. This could be related to the changed Co 2+ /Co 3+ redox mechanism, observed for y < 0.6 in our study and by Kosova et al 33 On the other hand, in the computational study of Malik et al, 67 the existence of solid-solution domains in LiFe 1-y Mn y PO 4 materials was speculated to originate from the random distribution of Mn 2+ , which leads to a mutual disturbance of the attractive Mn 2+ -Li + and repulsive Fe 3+ -Li + interactions.…”
Section: Partially Delithiated Electrodes-the Effects Of Co and Ni Smentioning
confidence: 99%
See 2 more Smart Citations
“…Note that the position of the redox peaks on the dQ/dV plots well corresponds to those of pure LFP, LVP and LTP, evidencing that low degree of substitution and the composite formation do not noticeably influence voltage of the redox processes upon cycling. On the contrary, in the case of the olivine-type solid solutions, e.g., LiFe 1-y Mn y PO 4 [20,21].…”
Section: Methodsmentioning
confidence: 99%